Profil Keterampilan Proses Sains Siswa SMA dalam Kegiatan Praktikum Pembuatan Eco-enzyme Berbahan Limbah Organik - Iin Murtini; Dika Agustia Indrati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the Science Process Skills (KPS) of grade XI Science students at SMAN 5 Tuban through the practicum of making eco-enzymes made from organic waste. The research uses a descriptive method with a quantitative approach and will be carried out in May 2025. The subjects in the study were 30 students of class XI Science-2 who were determined by purposive sampling technique. The research instrument is in the form of a science process skill observation sheet that has been validated by experts, while the data is analyzed using descriptive statistics. The results showed that students' basic Science Process Skills (KPS) in eco-enzyme material in the observation indicator with a percentage of 62.5% in the very good category, a classification of 75% in the good category, and a measurement of 62.5% in the very good category. Meanwhile, predictive skills obtained a percentage of 68.1% in the good category, attracted conclusions obtained 56.3% in the good category, and communicated results with a percentage of 25% classified as in the good category. Nevertheless, overall students have been skilled and appropriate in carrying out eco-enzyme practicum.